Rancangan Platform Galeri Bisnis Pada Inkubator Bisnis di Area Sub-Urban Dalam Meningkatkan Pemasaran UMKM - Tejo Nugroho; Syaifullah; Virginia Sarvatilova R S (Jurnal Manajemen dan Bisnis Kreatif)
Indonesia has the highest number SMEs in the ASEAN region. Employ 97% of the workforce, contribute 60.3% to GDP and 14.4% of national exports. However, the condition of Indonesian SMEs is still suboptimal, particularly in terms of access to financing and markets. This remains a major challenge for SMEs in expanding their businesses. SME incubator gallery platform is one solution to enhance collaboration with SME. Through this, SME can promote and market their products more widely and effectively. The platform facilitates connections with potential partners such as suppliers, distributors, and investors, who can assist in business development and expansion. The Canvas Business Lean method was employed in designing this platform. The outcome of this research is the Incubator Platform, which SME can utilize to enhance their business competencies. To join this platform, SME participants register through the platform and upon verification by the administrative team, they gain access to the provided features.